Immunoadsorption therapy and complement activation - Pták, J; Lochman, J (Transfusion and apheresis science, 2005)
Complement activation was studied in six patients treated with immunoadsorption columns Ig-ADSOPAK for myasthenia gravis. Mean therapy duration was 18.6 months (range 4-28 months). Prior and after each procedure, concentrations of C3 and C4 were examined, hemolytic activity of complement by a classic pathway (CH50) was determined, as well as terminal complement complex (TCC). After each immunoadsorption procedure, a decrease of C3 and C4 was noted (median 21.19% and 19.68%, respectively). The CH50 and TCC follow-up showed statistically significant complement activation. Median of TCC accrual was 60.21% and median of CH50 decrease was 23.24%. No clinical manifestations of complement activation were present. With increasing number of procedures a marked decrease of TCC activation was observed in five patients, which was statistically significant in three of them (p < 0.05). This finding may indicate an immunomodulating effect of long-term adsorption therapy. With increasing number of procedures, an inhibition in complement system reactivity occurs. This result, however, has to be confirmed on a larger group of patients.
Keywords: dospělí; Immunosorbent Techniques; Complement C3; separace krevních složek; Humans; lidé středního věku; Middle Aged; myasthenia gravis; aktivace komplementu; Complement Activation; Blood Component Removal; komplement C3; mužské pohlaví; komplement 4; Adult; Complement C4; Myasthenia Gravis; imunosorpční techniky; ženské pohlaví; lidé; Aged; senioři; Male; Female